KONSTRUKSI SOSIAL TEKNOLOGI CHATGPT DALAM PENDIDIKAN - Dienwati Nuris, Nisa; Anam, Khaerul; Narasati, Riri (Jurusan Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2024)
The technology that is currently developing in the field of education is the use of ChatGPT media. ChatGPT can be applied in campus learning. The flow of ChatGPT technology development poses a challenge to human perspectives on learning methods and information acquisition. The purpose of the research is to analyze the relationship between ChatGPT technology in shaping social constructs among students and institutions. This research uses the concept of the Social Construction of Technology (SCOT) to analyze the use of ChatGPT in the educational environment. This research method uses a descriptive qualitative approach to explore the meaning and experiences of students in using ChatGPT. To strengthen this qualitative research method, data collection techniques include in-depth interviews, direct observation, documentation, and literature review. The data analysis process follows systematic stages, namely data collection, data reduction through filtering relevant information, structured data presentation, and drawing conclusions based on the understanding of participants' experiences. The research results show that ChatGPT is designed to facilitate users in performing activities, with features tailored to users' activities. The implications of ChatGPT technology in education have both positive and negative impacts in its usage. The positive impact can assist in tasks, while the negative impact lies in aspects of privacy andand ethical limitations.